Determination of spectral markers of cytotoxicity and genotoxicity using in vitro Raman microspectroscopy: cellular responses to polyamidoamine dendrimer exposure. Issue 20 (12th September 2017) - Efeoglu, Esen; Casey, Alan; Byrne, Hugh J.
Abstract : Raman microspectroscopy as an in vitro label-free, high content screening technique to determine spectral markers of cytogenotoxicity. Abstract : Although consumer exposure to nanomaterials is ever increasing, with potential increased applications in areas such as drug and/or gene delivery, contrast agents and diagnosis, the determination of the cyto- and geno-toxic effects of nanomaterials on human health and the environment still remains challenging. Although many techniques have been established and adapted to determine the cytotoxicity and genotoxicity of nano-sized materials, these techniques remain limited by the number of assays required, total cost, and use of labels and they struggle to explain the underlying interaction mechanisms. In this study, Raman microspectroscopy is employed as an in vitro label-free, high content screening technique to observe toxicological changes within the cell in a multi-parametric fashion. The evolution of spectral markers as a function of time and applied dose has been used to elucidate the mechanism of action of polyamidoamine (PAMAM) dendrimers associated with cytotoxicity and their impact on nuclear biochemistry. PAMAM dendrimers are chosen as a model nanomaterial due to their widely studied cytotoxic and genotoxic properties and commercial availability. Point spectra were acquired from the cytoplasm to monitor the cascade of toxic events occurring in the cytoplasm upon nanoparticle exposure, whereas the spectra acquired from the nucleus and the nucleolus were used to explore PAMAM–nuclear material interaction as well as genotoxic responses.